1996
DOI: 10.1016/0014-5793(96)00975-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity of cathepsin B and other lysosomal enzymes in fibroblasts exposed to azithromycin, a dicationic macrolide antibiotic with exceptional tissue accumulation

Abstract: Azithromycin accumulates in lysosomes where it causes phospholipidosis. In homogenates prepared by sonication of fibroblasts incubated for 3 days with azithromycin (66 pM), the activities of sulfatase A, phospholipase AI, N-acetyl-~-hexosaminidase and cathepsin B increased from 180 to 330%, but not those of 3 non-lysosomal enzymes. The level of cathepsin B mRNA was unaffected. The hyperactivity induced by azithromycin is non-reversible upon drug withdrawal, prevented by coincubation with cycloheximide, affects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…First, AZM is a CAD and more than 50 marketed and experimental pharmaceuticals containing a CAD structure have been reported to elicit PLD (Sadrieh 2010). Second, AZM has been shown to promote the accumulation of phospholipids, cholesterol and lysosomal lamellar bodies in other cells (Gerbaux et al 1996; Munic et al 2011; Ribeiro et al 2009; Tyteca et al 2001; Van Bambeke et al 1998; Van Bambeke et al 1996). The hallmark feature, and indeed the gold standard, for identifying PLD is the demonstration of an intracellular accumulation of phospholipids and the concurrent development of lamellar bodies (Reasor and Kacew 2001; Sadrieh 2010).…”
Section: Discussionmentioning
confidence: 99%
“…First, AZM is a CAD and more than 50 marketed and experimental pharmaceuticals containing a CAD structure have been reported to elicit PLD (Sadrieh 2010). Second, AZM has been shown to promote the accumulation of phospholipids, cholesterol and lysosomal lamellar bodies in other cells (Gerbaux et al 1996; Munic et al 2011; Ribeiro et al 2009; Tyteca et al 2001; Van Bambeke et al 1998; Van Bambeke et al 1996). The hallmark feature, and indeed the gold standard, for identifying PLD is the demonstration of an intracellular accumulation of phospholipids and the concurrent development of lamellar bodies (Reasor and Kacew 2001; Sadrieh 2010).…”
Section: Discussionmentioning
confidence: 99%
“…3). Previous reports have shown that both nonselective, nonbasic cysteine cathepsin inhibitors (Kominami et al, 1987;Montenez et al, 1994) and lysosomotropic compounds, such as chloroquine (Gerard et al, 1988;Gerbaux et al, 1996), induce an increase of cathepsin and other lysosomal protein levels in both isolated cells and in vivo. The formation of a protein-ligand complex often results in protein stabilization toward thermal and chaotropic agent denaturation (Kleanthous et al, 1991), as well as protease susceptibility .…”
Section: Discussionmentioning
confidence: 99%
“…The affinity for PL A2 and its competitive inhibition have been variable among different amphiphilic substances 3 . These amphiphilic drugs have modulated the activities of other lysosomal enzymes including cathepsin B protease 50 . Enhanced activities of the lysosomal hexosaminidase, acid sphingomyelinase and sulfatase B in cells of the kidney cortex are considered to be due to a compensatory increase in degrading enzymes due to PL inhibition 51 .…”
Section: Possible Mechanismsmentioning
confidence: 99%